Market integration of grain legumes in India: the case of the chickpea market - Reddy, Amarender (SAARC Journal of Agriculture, 2014)
The present study assesses the market integration of chickpea in India from 2003 to 2010. The month end prices of chickpea for twelve markets in north India were used for the study. Out of twelve markets, only three markets are cointegrated, indicating weak integration of chickpea markets in India. However, the terminal markets located in major consuming (Delhi) and export/import locations (Dohad/Gujarat) clearly play an important role in price discovery and influences other domestic markets indicating the relevance of the import prices and large consuming centres on local market prices. Error correction terms indicate that the adjustment process from short-term disequilibrium in prices to long run price equilibrium is very slow. Overall, there is evidence of weak cointegration in the chickpea markets in North India and imports and major consuming centres are playing an important role in price discovery in domestic chickpea markets. DOI: http://dx.doi.org/10.3329/sja.v10i2.18320 SAARC J. Agri., 10(2): 11-29 (2012)